Escape room: Islamic banking challenge - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar; Ruslan, Mohd Firdaus; Mansor, Roseamilda (2025)
This paper outlines Escape Room: Islamic Banking Challenge, an interactive and student-centered teaching activity designed to enhance engagement and understanding of Islamic banking education across all levels of students. The activity places students in a simulated crisis, where they act as Shariah advisors working to unlock a bank’s system by completing a series of tasks related to Murabahah financing, types of Islamic contracts, relevant Qur’anic and Hadith sources, and Shariah compliance issues. The escape room activity is based on Kolb’s Experiential Learning Theory (1984), which emphasizes learning through experience, reflection, conceptualization, and experimentation. As such, this game offers students an opportunity to learn by solving real-world problems rather than passively receiving information from the lecturer. It also allows them to apply theoretical concepts within a contextually relevant scenario. Through this approach, students can connect theory to practice, collaborate with peers, and develop critical thinking skills. The activity is suitable for both traditional physical classroom settings and online platforms, making it adaptable to current teaching methods such as blended learning and Online Distance Learning (ODL). The inclusion of puzzles, numerical tasks, and ethical dilemmas makes the learning process more enjoyable, practical, and experience-based for students.